Embodied emotion impairment in Huntington's Disease. (July 2017) - Trinkler, Iris; Devignevielle, Sévérine; Achaibou, Amal; Ligneul, Romain V.; Brugières, Pierre; Cleret de Langavant, Laurent; De Gelder, Beatrice; Scahill, Rachael; Schwartz, Sophie; Bachoud-Lévi, Anne-Catherine
Abstract: Theories of embodied cognition suggest that perceiving an emotion involves somatovisceral and motoric re-experiencing. Here we suggest taking such an embodied stance when looking at emotion processing deficits in patients with Huntington's Disease (HD), a neurodegenerative motor disorder. The literature on these patients' emotion recognition deficit has recently been enriched by some reports of impaired emotion expression. The goal of the study was to find out if expression deficits might be linked to a more motoric level of impairment. We used electromyography (EMG) to compare voluntary emotion expression from words to emotion imitation from static face images, and spontaneous emotion mimicry in 28 HD patients and 24 matched controls. For the latter two imitation conditions, an underlying emotion understanding is not imperative (even though performance might be helped by it). EMG measures were compared to emotion recognition and to the capacity to identify and describe emotions using alexithymia questionnaires. Alexithymia questionnaires tap into the more somato-visceral or interoceptive aspects of emotion perception. Furthermore, we correlated patients' expression and recognition scores to cerebral grey matter volume using voxel-based morphometry (VBM). EMG results replicated impaired voluntary emotion expression in HD. Critically, voluntary imitation and spontaneous mimicry were equally impaired and correlated with impaired recognition. By contrast, alexithymia scores were normal, suggesting that emotion representations on the level of internal experience might be spared. Recognition correlated with brain volume in the caudate as well as in areas previously associated with shared action representations, namely somatosensory, posterior parietal, posterior superior temporal sulcus (pSTS) and subcentral sulcus. Together, these findings indicate that in these patients emotion deficits might be tied to the "motoric level" of emotion expression. Such a double-sided recognition and expression impairment may have important consequences, interrupting empathy in nonverbal communication both ways (understanding and being understood), independently of intact internal experience of emotion.